Perspectives from the Hmong Population on Type 2 Diabetes - Sarah M. Westberg, PharmD, BCPS; Phoua Xiong, Pharm.D (University of Minnesota Libraries Publishing, 2012)
The primary goal of the study was to determine perceptions the Hmong population has about Type 2 diabetes. Specific information to be gathered from the Hmong participants were: reactions after being diagnosed with Type 2 diabetes, knowledge and beliefs about medications, and how pharmacists can help them with their diabetes care. Learning the beliefs of this population related to Type 2 diabetes will help identify methods to improve diabetes care and education for Hmong patients. A focus group was conducted with Hmong participants with Type 2 diabetes to explore their perceptions and experiences with diabetes. There were 9 participants in the focus group which lasted approximately 90 minutes. The major themes were a misunderstanding of diabetes and its treatment, a reluctance to adhere to medications, a reluctance to change cultural diet, and the need for clear education from pharmacists. Participant recommendations for pharmacists were to improve their diabetes care by educating them about the condition, medication, and available treatments.